National plans to address adaptation and mitigation in agriculture: An analysis of Nationally Determined Contributions - Richards, Meryl B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Data presented here are the result of an analysis of the mitigation contributions of the 177 NDCs submitted as of February 5, 2019. This database is a limited updated to the INDC database published previously (https://hdl.handle.net/10568/73255). A full upate is forthcoming. Data were collected directly from NDC submisions, which can be found at: https://www4.unfccc.int/sites/NDCStaging/Pages/All.aspx